(untitled) (International Journal on Stereo & Immersive Media, 2025)
The concept of immersion is addressed by a broad range of tools in contemporary art. Some techniques seen in large-scale installations, which have been used in museums and mass entertainment venues since the 19th century, such as physical visual effects and mirrors, continue to play a significant part. With newly developed digital technologies like projection mapping and large LED screens, immersion has reached enormous popularity in our time. As a result, there is a demand for a changing attitude in art spectatorship. Immersive participation does not only involve the viewers themselves but also their social media behavior. This challenges artists and curators to embrace the new model of spectatorship and find a balance between artistic design and market demands.